TECHNOLOGY AND JUSTICE: THE PUBLIC DEFENDER'S OFFICE OF TOCANTINS AS A MODEL OF INNOVATION AND INCLUSION (Editora Impacto Científico, 2025)
Technological advances and the adaptation of Brazilian legal institutions, driven by the COVID-19 pandemic, have transformed access to justice. This study analyzes the challenges faced and the strategies adopted within the national and Tocantins justice systems to ensure the continuity of services during this period. The research focuses on the modernization of the Public Defender's Office of the State of Tocantins (DPE-TO) between 2020 and 2024, highlighting the implementation of virtual services and their subsequent consolidation into a hybrid model, which combines in-person and remote services. In addition to ensuring the provision of legal services in critical times, this innovation has expanded accessibility for vulnerable populations in remote regions. The study seeks to analyze virtual services as a modernization tool that transcends the scope of access to justice, contributing to the strengthening of citizenship, the Democratic Rule of Law, and regional development. To support the analysis, the study adopts a mixed methodological approach, combining qualitative and quantitative techniques. To this end, it is based on a literature review and the analysis of statistical data provided by the institution, allowing an objective assessment of the evolution of services throughout the period analyzed. The results demonstrate that, while virtual services played a fundamental role during the pandemic, in-person services regained predominance in the post-pandemic context.